Keefektifan Kemampuan Menulis Kreatif Siswa SD dengan Model Pembelajaran Multiliterasi - Dafit, Febrina (GERAM: Gerakan Aktif Menulis, 2017)
The low ability of writing creative skill of elementary students become the background of this research. The purpose of this study is to review and describe the effectiveness of creative writing skills of elementary students with multiliteration learning model. Creative writing is a way or process of ideas, or messages that contain added value, uniqueness, and is the original work of the author. Learning multiliteracy is a learning that constantly uses language skills to learn and form a complex understanding of other knowledge, related knowledge in the process of inquiry and as a means of building knowledge, building meaning, channeling ideas, and expressing ideas to generate creative and critical ideas for knowledge Already owned to be communicated to others. The method used in this research is quasi experiment with non-equivalent control group pretest posttest design. Data collected to answer research question that is data of pretest and posttest result of writing ability of fourth grader of elementary school. Techniques to measure the ability to write creative essay techniques. The result of posttest average score of writing ability of experiment class student is 9,04, meanwhile posttest average score of writing student ability of class of control is 7,38. From the results of these studies show that students creative writing ability is effective with in learning multiliteracy model